Multinational Teams in European and American Companies - Aida Hajro (Peter Lang International Academic Publishers, 2008)
Incorporating team context into research and practice concerning team effectiveness in multinational organizations still remains an ongoing challenge. This book aims at drawing the attention of researchers and practitioners towards the importance of various `layers' of context on multinational teams and developing an empirically derived framework for multinational team functioning in business organisations. It shows how companies make use of these teams and how these teams contribute to competitive advantage. The study has been conducted in an Austrian, a German, and an American company. It reveals that if managed appropriately, these teams reduce the complexity of operations by facilitating the creation and transfer of explicit and tacit knowledge and by transferring appropriate dimensions of headquarter corporate culture between geographically dispersed business units.
Keywords: 330